Exploring the role of the vaginal microbiome in HPV infection dynamics: A prospective cohort study - Yiran Liu; Ran Li; Jun Liu; Xiaolong Liang; Mingrui Su; Shuzhen Wang; Boran Mu (iScience)
Summary: Persistent human papillomavirus (HPV) infection is a key risk factor for cervical cancer, often associated with changes in the vaginal microbiome (VMB). High-throughput 16S rRNA sequencing was used to study the VMB in a prospective cohort of 731 individuals. Participants were monitored through two follow-up screenings and then categorized into two groups: 22 female patients with persistent HPV infection (PHI), 31 female patients who cleared the infection (HC). After excluding those with HPV and other urogenital infections, 43 female patients were selected as controls, and their samples were analyzed using the same high-throughput sequencing method. Results indicate that high-risk HPV infections correlate with increased microbial diversity and reduced Lactobacillus levels. Even after HPV clearance, distinct microbial differences persist, suggesting that VMB could serve as a biomarker for monitoring infection and cervical health management, especially in populations at higher risk.